Cerebrotendinous xanthomatosis tremor successfully controlled post-ventral intermediate nucleus-deep brain stimulation: a case report - Rich, Alyson M.; Karakoleva, Ema V.; McInerney, James; Farace, Elana; De Jesus, Sol (Frontiers in Neurology, 2023)
Cerebrotendinous xanthomatosis (CTX) is a rare autosomal recessive disorder caused by a deficiency of the sterol 27-hydroxylase enzyme. This deficiency results in excess production and accumulation of cholestanol, which can lead to many clinical findings within the first three decades of life, including progressive neurological dysfunction. This is a treatable condition with improvements in neurological and non-neurological symptoms upon the early initiation of replacement therapy. This case report details a 42-year-old left-handed male in whom DBS intervention was pursued due to a limiting tremor related to delayed diagnosis and treatment of CTX at 22 years old. The application of DBS in treating tremors in a CTX patient has not previously been reported. For our patient, application of DBS led to meaningful and longstanding tremor control benefits that have required minimal changes to stimulation parameters post-DBS. These improvements to tremor were achieved without negative impact to his other CTX related comorbidities.